Memperkuat Presidensialisme Multipartai di Indonesia: Pemilu Serentak, Sistem Pemilu, dan Sistem Kepartaian - Djayadi Hanan (Jurnal Universitas Paramadina, 2016)
Abstract Strengthening governmental system has been the subject of public and scholarly discussion in Indonesia since a multiparty presidential system has been adopted in this country since 2004. There is a widely spread assumption that the implementation of concurrent election (legislative and presidential) is one of the main ways to do so because it will simplify the number of political parties in the legislature which will help the president (the executive) to govern more effectively. Is this assumption right? What do the theories and empirical evidence say about it? Using comparative politics perspective and analysis, this article argues that the implementation of concurrent election is not a necessary and sufficient condition for the strengthening of Indonesia’s multiparty presidential system. There are many variables that need to be combined with it. The electoral systems of plurality and majority run-off, for example, will have different impact to presidential system when combined with concurrent election.